2014
DOI: 10.17219/acem/37036
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Heavy Chain/Light Chain Pairs (Hlc, Hevylitetm) Assays for Diagnosing and Monitoring Monoclonal Gammopathies

Abstract: Immunofixation (IFE) is a standard method for detecting monoclonal immunoglobulins and characterizing its isotype. Recently clonality can also be determined by using immunoglobulin (Ig) heavy chain/light chain immunoassays -HLC, Hevylite TM . HLC separately measures in pairs light chain types of each intact Ig class generating ratios of monoclonal Ig/uninvolved polyclonal Ig concentrations. Studies have shown that HLC and IFE are complementary methods. HLC assays quantify monoclonal proteins and identify monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Recently clonality can also be determined by using immunoglobulin (Ig) heavy chain/light chain immunoassays (HLC), Hevylite. HLC separately measures in pairs light chain types of each intact Ig class generating ratio of monoclonal Ig/uninvolved polyclonal Ig concentrations [80]. Studies have shown that the HLC ratio (HLCR) is of prognostic significance in MM.…”
Section: Monitoring Of Response Toolsmentioning
confidence: 99%
“…Recently clonality can also be determined by using immunoglobulin (Ig) heavy chain/light chain immunoassays (HLC), Hevylite. HLC separately measures in pairs light chain types of each intact Ig class generating ratio of monoclonal Ig/uninvolved polyclonal Ig concentrations [80]. Studies have shown that the HLC ratio (HLCR) is of prognostic significance in MM.…”
Section: Monitoring Of Response Toolsmentioning
confidence: 99%
“…Clinically applied assay ("IgM Hevylite immunoassay") for monoclonality identification, prognosis prediction and monitoring response to treatment in multiple myeloma has recently been developed [10] and justified as a reliable progression marker in the monitoring of monoclonal gammopathies but not suited for diagnostics [14][15][16][17][18][19][20][21]. It relies on antibody binding to the epitopes spanning the junctional regions between either k or l light chain and their respective heavy chain partners.…”
Section: Monitoring Of Igm-mm and Wm Patientsmentioning
confidence: 99%
“…O MM é uma neoplasia maligna, de caráter progressivo e incurável que acomete células B. A proliferação das células plasmáticas (plasmócitos) na medula óssea é descontrolada, com produção e secreção de imunoglobulinas (Ig) anômalas monoclonais ou fragmentos dessas, chamadas de proteína M [8][9][10][11] . Estruturalmente, as imunoglobulinas normais são compostas de unidades menores, as cadeias pesadas e leves.…”
Section: Introductionunclassified
“…Para o diagnóstico do tipo de mieloma, utiliza-se a eletroforese para identificação dessas cadeias 7 . Apesar da variedade de manifestações clínicas, como anemia grave, hemorragias 11 , leucopenia 13 , lesão óssea, insuficiência renal e infecção recorrente, infiltração de plasmócitos neoplásicos, produção de imunoglobulinas anômalas em excesso, supressão ou perda da função de anticorpos da imunidade humoral 14 , a maioria dos pacientes é diagnosticada nos estágios avançados da doença e as taxas de sobrevida em cinco anos após o diagnóstico é de apenas 35%…”
Section: Introductionunclassified